Profile of match performance and heart rate response in Japanese amputee soccer players - Maehana, H.; Miyamoto, A.; Koshiyama, K.; Tanaka Yanagiya, T.; Yoshimura, M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this study was to profile the match performance and heart rate response in Japanese amputee soccer players. METHODS: Twelve amputee soccer players participated in this study. Match data were collected 20 samples in 4 matches. Match performances data such as total distance, high-intensity running (HIR: =13 km/h) were collected using a global positioning systems technology. Heart rate (HR) was recorded using short-range radio telemetry. In addition, the rating of perceived exertion (RPE) was assessed immediately using Borg`s original after the first half and the second half. RESULTS: This study showed that the distance covered over the 50 minutes of the match was 2984.2±56.1 m, and it was significantly shorter in the second half than the first half (P<0.05). The distance covered by HIR was 205.3±100.5 m, and there was no significant difference between the first half and the second half. Moreover, the mean HR during match was 176.8±7.9 beats/min, which corresponded to 96.3% of HRmax. RPE was a high value of more 15 in both of the first half and the second half. CONCLUSIONS: This study was the first to evaluate competitive performance during matches in amputee soccer. Results of this study indicated that the exercise intensity was high in amputee soccer. It would be considered that causes were amputee soccer own rules and exercise style. These findings would serve as the reference when advance the future studies of amputee soccer.